A New Type Microwave Absorption Materials: Metal–Organic‐Frameworks (MOFs) Used as Non‐Conductive Material Combination with P‐C‐800 - Guodong Han; Song Zhao; Sai Sui; Bo Feng; Yudeng Wang; Junxiang Zhou; Zhuolun Li; Xiaoxia Tian; Yuxiang Jia; Jiafu Wang; Shaobo Qu (Advanced Electronic Materials)
Abstract Metal–Organic‐Frameworks (MOFs) are commonly used as microwave‐absorbing materials after pyrolysis treatment. Rare researchers treat MOFs as non‐conductive materials and use them as absorbing materials directly. In this paper, MOFs@P‐C‐800 composite materials are prepared adopt to hydrothermal and ultrasonic dispersion methods by regulating the morphological characteristics of MOFs and the content of P‐C‐800. As for the Co‐BDC‐P‐C‐800, the maximum reflection loss reaches −18.4 dB at 14.29 GHz and the effective absorption bandwidth (EAB) achieves 3.87 GHz from 13.5 to 17.37 GHz. After the contents of P‐C‐800 is adjusted, the Co‐BDC‐P‐C‐800 (0.05 g) exhibited excellent microwave absorption performance, the maximum RL value of −60 dB at 13 GHz with a thickness of 2.0 mm, and the EAB achieves 5.91 GHz from 12.02 to 17.93 GHz. This paper not only provides new application direction for MOFs, but also offers a promising direction for the research and development of absorbing materials.